The Accuracy of Pulse Spectroscopy for Detecting Hypoxemia and Coexisting Methemoglobin or Carboxyhemoglobin. (June 2016) - Kulcke, Axel; Feiner, John; Menn, Ingolf; Holmer, Amadeus; Hayoz, Josef; Bickler, Philip
Abstract : BACKGROUND: Pulse spectroscopy is a new noninvasive technology involving hundreds of wavelengths of visible and infrared light, enabling the simultaneous quantitation of multiple types of normal and dysfunctional hemoglobin. We evaluated the accuracy of a first-generation pulse spectroscopy system (V-Spec™ Monitoring System, Senspec, Germany) in measuring oxygen saturation (SpO2 ) and detecting carboxyhemoglobin (COHb) or methemoglobin (MetHb), alone or simultaneously, with hypoxemia. METHODS: Nineteen volunteers were fitted with V-Spec probes on the forehead and fingers. A radial arterial catheter was placed for blood sampling during (1) hypoxemia with arterial oxygen saturations (SaO2 ) of 100% to 58.5%; (2) normoxia with MetHb and COHb increased to approximately 10%; (3) 10% COHb or MetHb combined with hypoxemia with SaO2 of 100% to 80%. Standard measures of pulse-oximetry performance were calculated: bias (pulse spectroscopy measured value − arterial measured value) mean ± SD and root-mean-square error (Arms ). RESULTS: The SpO2 bias for SaO2 approximately 60% to 100% was 0.06% ± 1.30% and Arms of 1.30%. COHb bias was 0.45 ± 1.63, with an Arms of 1.69% overall, and did not degrade substantially during moderate hypoxemia. MetHb bias was 0.36 ± 0.80 overall and stayed small with hypoxemia. Arms was 0.88 and was <3% at all levels of SaO2 and MetHb. Hypoxemia was also accurately detected by pulse spectroscopy at elevated levels of COHb. At elevated MetHb levels, a substantial negative bias developed, −10.3 at MetHb >10%. CONCLUSIONS: Pulse spectroscopy accurately detects hypoxemia, MetHb, and COHb. The technology also accurately detects these dysfunctional hemoglobins during hypoxemia. Future releases of this device may have an improved SpO2 algorithm that is more robust with methemoglobinemia. Abstract : Published ahead of print April 22, 2016